The awareness level on the value management implementation among developers - Jumaan, Zaishafika Erma (2022)
The sector that contributes most to the growth of other sectors in a country is the construction industry. The development of value management (VM) is still less aware even though several construction projects have been successfully finished. Value management can be defined as one of the services that decisions made by the client against in the value system to maximize the functional of development from the initial stage until the completion of project. Value Management involves a multidisciplinary team of individuals to improve project performance while accounting for cost and function. The value management practice is not widely used in Malaysia. Due to this scenario, this research aim is to expand the awareness on implementation of value management among developers and encourage developers to apply value management in their projects. Hence, the objective for this research is to identify the level of awareness on the value management implementation among developers, determine the challenges that developers faced while implementing the Value Management method and recommend strategies to increase the level of uses on the value management implementation among developers. In this study, quantitative methods have been used, and 148 questionnaires have been distributed where the return was 103 respondents.